WACANA PERSAHABATAN DALAM KUMPULAN SATUA I PUNYAN KEPUH TEKEN I GOAK - Yuliawati, Ni Nyoman (Humanis; Volume 6. No. 3. Maret 2014)
Research "Discourse Friendship in corps Satua I Punyan Kepuh teken I Goak" to know and comprehend meaning which consist in it. Basis for theory which is used in this research is semiotik theory laid open by De Saussure. Method And technique which is used in this research is divided to become three step, that is ( 1) ready Phase of data use method correct reading, by translation technique and record-keeping technique. ( 2) Phase analyse data use method qualitative and analytic descriptive technique. ( 3) Phase presentation result of data analysis use informal method and technique think inductive deductive. Result of which is obtained from this research is entitas mean at Discourse Friendship in crops Satua I Punyan Kepuh teken I Goak, that is positive meaning of friendship to construct to feel association, candidness and reaching of prosperity
Keywords: satua, discourse, meaning.